Pengaruh Bimbingan Kelompok terhadap Kemandirian Emosional Siswa - Ramadhanis, Nadia; Umari, Tri; Khadijah, Khairiyah (Lembaga Yasin AlSys, 2025)
Adolescence is a developmental phase that is vulnerable to both internal and external emotional pressures, which often results in low emotional independence. Preliminary findings at SMP Negeri 2 Teluk Kuantan revealed students with high levels of dependency when facing personal and social problems. This study aims to examine the effect of group counseling services on improving students’ emotional independence. A quantitative approach was used with a one-group pretest-posttest experimental design. The research subjects consisted of nine students purposively selected based on criteria of low emotional independence. Instruments included an emotional independence questionnaire and an observation sheet, both of which had been tested for validity and reliability. Data were analyzed using descriptive statistics and N-gain test with the assistance of SPSS version 23. The results showed that group counseling services had a positive impact on increasing students’ emotional independence, with an average N-gain score of 0.47, categorized as moderate improvement. These findings indicate that group counseling is effective as an intervention strategy to develop students’ emotional independence. The implications of this study highlight the importance of optimizing the role of guidance and counseling teachers in designing and implementing services that support students’ emotional development in an independent and adaptive manner.